Mitigating the macroeconomic impact of severe natural disasters in Africa: Policy synergies - Samba Diop; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2021)
This study evaluates the economic impact of severe natural disasters in Africa using the generalized synthetic control method. In other words, it assesses how gross domestic product (GDP) would have been affected if severe natural disasters did not occur. Moreover, it explores the determinants of the destructiveness of the impact, focusing on the role played by capital. We find that severe natural disasters induce a significant and continuous reduction of GDP many years after the event. Indeed, economic losses caused by disasters depend on the level of capital (human capital, employment and capital stock) and aspects of governance quality (political stability and absence of violence). In other words, negative synergies are apparent because while capital stock, employment and human capital unconditionally reduce the macroeconomic impact of natural disasters, the corresponding conditional or interactive effects with political stability are also negative. Policy implications are discussed.
Keywords: Q54; O17; O55; P1; 330; natural disasters; economic growth; Africa